Analisis Peluang Dan Ancaman Perdagangan Produk Perikanan Dan Kebijakan Untuk Mengatasinya : Studi Kasus Indonesia dengan Malaysia dan Vietnam - Lis Nurdiana; Daspar Daspar (Journal of Business Economics and Management | E-ISSN : 3063-8968, 2025)
This study analyzes the dynamics of Indonesia’s fisheries trade with Malaysia and Vietnam, two countries that serve as both strategic partners and competitors in the Southeast Asian region. Indonesia holds significant potential in marine resources, yet struggles to compete in the export of high-value processed products. Key challenges include limited cold chain infrastructure, low logistics efficiency, and underdeveloped downstream policies. Malaysia excels in distribution and processing, while Vietnam leads in production efficiency and technological advancement. To strengthen Indonesia's trade position, an integrative policy approach is needed, involving product competitiveness, regional cooperation, and local industry protection. This paper recommends the development of integrated marine industrial zones and incentives for small-scale enterprises to reduce import dependency and expand export markets.